Identification of new position of DNA insertion and 24-bp INDEL mutation polymorphism in prolactin gene promoter of Thai native chickens - Thanaset Thongsaiklaing; H. Datumada; John G. Morris; Hataichanok Passara (International Journal of Agricultural Technology, 2025)
This research identified a 24-bp INDEL (-358) on the promoter region of the PRL gene in Thai native chickens. The allele frequencies for allele I and allele D were 0.20 and 0.80, respectively. The genotype frequencies were II (0.028), ID (0.349), and DD (0.622), respectively. The heterozygosity values comprised the Ho (0.350), higher than the He value (0.323). Moreover, our findings revealed new DNA duplication on the PRL promoter region, with three distinct polymorphisms of 30 bp (-358), 24 bp (-358), and 14 bp (-358), respectively.
Keywords: Growth Hormone and Insulin-like Growth Factors; Hypothalamic control of reproductive hormones; Genetic and Clinical Aspects of Sex Determination and Chromosomal Abnormalities